PERBANDINGAN ESTIMASI USIA DENTAL DENGAN METODE CORONAL PULP CAVITY INDEX (CPCI) PADA GIGI PREMOLAR PERTAMA DAN MOLAR PERTAMA RAHANG BAWAH USIA 20 – 50 TAHUN BERDASARKAN RADIOGRAFI PANORAMIK - Salsabila Rasya WIjaya; Moch Atmaji Windrianto; Okky Marita Ardy (Lembaga Penelitian Universitas YARSI, 2026)
Background: Dental age estimation is possible due to stable morphological changes in teeth, particularly secondary dentin deposition. The Coronal Pulp Cavity Index (CPCI) assesses changes in coronal pulp size, but its use in the Indonesian population is limited. Objective: To compare dental age estimation of the mandibular first premolar and first molar using the CPCI method on panoramic radiographs and to review it from an Islamic perspective. Methods: This cross-sectional study analyzed 81 panoramic radiographs of patients aged 20–50 years. Dental age was estimated using the Tooth Coronal Index (TCI) and analyzed with linear regression and paired t-test. Results: TCI showed a significant correlation with chronological age in premolars (r = 0.657; R2 = 0.432) and molars (r = 0.664; R2 = 0.441) (p < 0.001). The first molar demonstrated a smaller age deviation than the first premolar. Conclusion: CPCI-based age estimation using the mandibular first molar is more accurate and consistent with Islamic principles of justice and maslahah.